Teaching English in Multilingual Contexts: Teachers' Perspectives - Paudel, Pitambar (Prithvi Academic Journal, 2020)
The national and international migration has made multilingualism a common phenomenon; Nepal is no exception. Nepal is regarded as a multilingual country where more than 129 languages are spoken. Despite multilingualism, English language has been taught from basic to advance levels of education as a core or optional subject. In this context, this article has investigated challenges faced by English teachers in teaching English in multilingual classes of Nepal. The article has also attempted to explore the strategies employed by teachers to deal with the challenges that they faced. To achieve these objectives, explanatory sequential mixed research design was used. Eighty basic level English language teachers from forty different (2 from each) schools of Kaski district were selected purposively. The data was collected through survey questionnaires, interview and classroom observation. The research showed that linguistic diversity, students classroom behavior and demotivation towards English, uncontextual and lengthy syllabus, lack of teachers' involvement in curriculum designing process and refresher courses programmes were the major challenges that the teachers have faced while teaching English. The research also indicated that the use of translation, use of increasing reading materials, managing rewards to the students, and repetition of the text were the major strategies that teachers employed to cope with the challenges in multilingual contexts. This implies that the policy makers, curriculum designers, and administrators should train the teachers to address these issues that are related to teaching English in a multilingual context like in Nepal.